1992
DOI: 10.1152/jn.1992.68.5.1624
|View full text |Cite
|
Sign up to set email alerts
|

Saccade-vergence interactions in humans

Abstract: 1. We recorded eye movements in four normal human subjects during refixations between targets calling for various combinations of saccades and vergence. We confirmed and extended prior observations of 1) transient changes in horizontal ocular alignment during both pure horizontal saccades (relative divergence followed by relative convergence) and pure vertical saccades (usually divergence for upward and convergence for downward saccades); 2) occasional, high-frequency (20-25 Hz), conjugate oscillations along t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
266
1
18

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(307 citation statements)
references
References 17 publications
22
266
1
18
Order By: Relevance
“…For almost all of the present subjects, the majority of fixations ended in a more converged eye position, a finding more consistent with the early observations of vergence in reading by Schmidt (1917), than those by Clark (1935) and Taylor (1966) who reported observing only divergence during fixations. The present finding of convergence during fixations in reading also A .\ \ \ Hendriks / Acm Psychologicu 92 I ¡996) corresponds with the results of more recent studies in which LEDs were used as stimuli (Collevvijn et al, 1988a;Zee et al, 1992).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For almost all of the present subjects, the majority of fixations ended in a more converged eye position, a finding more consistent with the early observations of vergence in reading by Schmidt (1917), than those by Clark (1935) and Taylor (1966) who reported observing only divergence during fixations. The present finding of convergence during fixations in reading also A .\ \ \ Hendriks / Acm Psychologicu 92 I ¡996) corresponds with the results of more recent studies in which LEDs were used as stimuli (Collevvijn et al, 1988a;Zee et al, 1992).…”
Section: Discussionsupporting
confidence: 89%
“…Previous research with LEDs has shown that vergence velocity during the initial part of a fixation period decreases as a function of the length of the preceding saccade (Collewijn et al, 1988a;Zee et al, 1992). To investigate whether this relationship exists in reading and whether vergence velocity could also be affected by the experimental manipulations directly, an additional analysis was carried out on the vergence velocity data of the Text Type and the Reading Objective experiment (to control simultaneously for the effect of differences in fixation duration, vergence velocities of the initial 80 ms of the fixations were used).…”
Section: 3 Saccade Size and Vergence Velocitymentioning
confidence: 99%
“…Although the effects of saccades on vergence velocity have been extensively reported (Enright 1984;Kenyon et al 1980;Ono and Nakamizo 1978;Zee et al 1992), the possibility that vergence might have some effect on saccades has attracted much less attention. In studies with humans, horizontal saccades during vergence often showed slower velocities and resulted in longer durations than conjugate saccades of comparable size (Collewijn et al 1995;Erkelens et al 1989) but the effects of vergence on vertical saccades were less clear (van Leeuwen et al 1998).…”
Section: Opns and Saccadic Slowingmentioning
confidence: 99%
“…In studies underway, we are testing this hypothesis using mathematical models that describe the normal behaviour of the eye muscles and fascia (ocular motor plant) during saccades. 19 Do any prior reports support our hypothesis?…”
Section: Discussionmentioning
confidence: 74%